(3QSGdI aj MLjI eaghe GdChdhjIs - (3GdWHGWHGFj, GdcGXej, GdMGFQj, GdCUHgGfj, Ydj Hf eMeO Ydj Hf CHj GdeYGdj, J (B1231 (3gs
(3ChdgG (B:s
(3GdMeO ddg (B.. (3Efg bO HdZJfj QSGdJc aj djdI GdLeYI GdMGOjI YTQ ef TgQ ThGd (B... (3GddaX GdOGd YdjgG efbhdG YQajG Ch Cf OdGdJg Ydjg OdGdI EdJRGejI ceG gh GdCbhi hcja cGf agj ef CbSGe GdOdGdI GddaXjI jTedgG LejY eG bOefGg (B...s
(3BNQgG (B:s
... (3aeG CageJg heG JHjf JjSQ GdedGMXI dVjb GdhbJ hGdGSJYLGd ZGjI GdGSJYLGd GdbGadI HGdeSGaQI acJHJg aj GddjdI GdePchQI eY GdHGd HGdHGd hGNJdGa GdMGd hcKQI GdGTJZGd(B.. (3JeJ GdQSGdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\ 17s
(3GdPQjYI (B6\1522s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs